The Transformative Role of Mobile Applications in Digital Banking: A Comprehensive Analysis of Customer Engagement and Service Evolution - Jaspreet Kumar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The digital transformation of banking services through mobile applications represents a pivotal shift in the financial services industry, fundamentally changing how customers interact with their financial institutions. This comprehensive article research examines the multifaceted role of mobile applications in driving digital banking transformation, with particular emphasis on security implementations, customer engagement strategies, and the impact of automation and personalization on service delivery. The article analyzes the critical aspects of mobile banking infrastructure, including multi-layered security protocols, regulatory compliance frameworks, and technological integration strategies that have shaped the modern banking landscape. Special attention is given to the accelerated digital adoption during the COVID-19 pandemic, which served as a catalyst for unprecedented changes in banking behavior and technological advancement. Through analysis of industry data and expert insights, this research demonstrates how mobile banking applications have evolved from simple transaction tools into sophisticated platforms that integrate advanced security protocols, artificial intelligence, personalized analytics, and seamless customer engagement features. The article reveals significant improvements in customer satisfaction, operational efficiency, and service accessibility, with mobile banking users showing an increase during the pandemic period and an increase in customer engagement for institutions implementing advanced analytics and personalization strategies. This article contributes to the understanding of mobile banking’s evolutionary trajectory and provides valuable insights for financial institutions seeking to enhance their digital banking capabilities in an increasingly competitive landscape.